PENGEMBANGAN MODUL KIMIA BERBASIS MULTIMEDIA UNTUK MAHASISWA JURUSAN TEKNIK MESIN POLITEKNIK NEGERI BALI - Ida Ayu Anom Arsani (Soshum: Jurnal Sosial dan Humaniora, 2014)
The use of multimedia technology in education is very supportive to efficiency and effectiveness of teaching and learning process. In the field of Chemistry, multimedia is used to present concepts of chemistry at level of macroscopic, sub-microscopic, and symbolic. This module development is intended to provide students with teaching resources for their selfdirected learning. In order to know criteria of feasibility of the draft, some validation had been done including content validation and media validation. The average percentage values obtained in media and design validation module is 93.75% and 85.42%. This value indicates that no revisions of the modules developed. In one-two-one evaluation was 85.01%, small group evaluation was 84.36%, and field trial was 82.27%. The revision is based on comments and suggestions from the validator. This is done to improve the developed draft. There are significant differences in students' learning achievement, based on results of pretest and posttest conducted, This means that the development of multimedia modules have positive impact on student learning outcomes.